The early school leaving: evolution and affected groups - Recio Muñoz, Miguel; de la Cruz Hernández, Manuel (Avances en Supervisión Educativa, 2011)
Nowadays one of the most important challenges from a social analysis perspective of education is referred to early school leaving rate in the context of all school academic performance indicators. This indicator has been selected by the European Union to evaluate the progress of Lisbon Objectives achievement to reach the knowledge society. This objective has as a goal that the maximum amount of population has higher qualification lever than compulsory schooling. The article analyses early school leaving indicator from two perspectives: On the one hand, the evolution and geographic distribution and on another hand its impact and the age when the school leavers appears.